Identifying social determinants of health in populations exposed to structural inequities: a qualitative study of the COVID-19 pandemic experiences of Black and Latinx people living with HIV and cardiovascular risks - Loeb, Tamra Burns; Albarran, Graciela I.; Lee, Ethan; McEwan, Jenna Alarcon; Dyer, Karen E.; Cooley-Strickland, Michele; Norwood-Scott, Enricka; Ramm, Kate; Kesblyan, David; Barnes, Aleeja; Novacek, Derek; Chin, Dorothy (Frontiers in Public Health, 2024)
Introduction Black and Latinx communities experience inequities in the social determinants of health (SDOH) and high rates of chronic illnesses [e.g., cardiovascular disease (CVD), HIV]. The COVID-19 pandemic amplified these long-standing SDOH disparities. However, scant attention has been paid to the pandemic-related experiences of populations exposed to structural inequities. Methods Using a semi-structured interview guide, 60 in-depth telephone interviews were conducted with Black and Latinx people living with HIV (PLWH) and CVD risks to assess: (1) perceived personal and community risk for COVID-19; (2) knowledge of and access to COVID-19 public health information; (3) barriers to COVID-19 public health recommendations and vaccine uptake; and (4) perceptions of HIV, CVD, and COVID-19. Interviews were professionally transcribed into either English or Spanish. Spanish transcripts were translated into English. Rapid qualitative analysis was used to summarize each transcript into a structured templaicte corresponding to interview guide domains. Summaries were combined into matrices for identification and comparison of themes across domains. Results Participants reported risks for COVID-19 due to being immunocompromised and SDOH, including transportation, exposure to risks conferred by others, living in under-resourced neighborhoods, and housing insecurity. Participants engaged in protective countermeasures by adhering to public health mandates. Relationships with providers, participating in community support groups, and digital inclusion and literacy were salient with respect to dissemination of COVID-19 information and vaccine uptake. Experiences with managing a chronic illness facilitated vaccine acceptance. Participants described language barriers, experiences of discrimination, and a historical lack of trust in medical systems and vaccines. Discussion This study provides a real-time narrative from PLWH and CVD risks who were vulnerable during the height of the COVID-19 pandemic. Implications include the need for continuity with providers and established community networks, increasing internet access and digital health literacy, and addressing historical trauma incurred in medical settings. It is critical to understand the impact of traditional SDOH on those living with chronic illness as well as other social determinants that shed light on access to public health information, adherence to public health recommendations, and vaccine uptake among populations exposed to structural inequities.